Effector-assisted breeding for bacterial wilt resistance in horticultural crops - Jayaraman, Jay; Segonzac, Cécile; Cho, Heejung; Jung, Gayoung; Sohn, Kee Hoon (Horticulture, environment and biotechnology, 2016)
Ralstonia solanacearum ( Rso ) is a causal agent of bacterial wilt disease in a wide range of horticultural crops. Rso strains are heterogeneous in nature and are therefore difficult in terms of both classification and development of disease resistance. Rso pathogen-associated molecular patterns (PAMPs) and effector proteins are secreted into plant cells, where they respectively activate and suppress plant immunity, thereby affecting Rso virulence. We review the current knowledge of Rso disease resistance and efforts to generate Rso -resistant crop plants. Further, we propose the introduction into plants of known pattern recognition receptors (PRRs) that recognize Rso PAMPs in order to confer resistance to a large number of strains. Additionally, the conserved ‘core’ effectors from Rso phylotypes could be used to identify and deploy nucleotide-binding leucine-rich repeat (NLR) resistance genes in a desired crop cultivar. We suggest that a phylotype-specific effector-assisted breeding program be instituted to rapidly identify disease resistance genes in available plant germplasm collections. Furthermore, stacking multiple NLRs that recognize Rso effectors would provide durable disease resistance by minimizing the chance for Rso to evade the implemented resistance. Finally, we propose that this strategy would most efficiently be achieved through development of transgenic crop lines.